"It's not something I've really thought about 'til now'": The social aspects of U.S. emerging adults' comics reading histories. (March 2023) - Moeller, Robin A.
The common image of a reader is that of a person alone with a book, but reading is actually a social activity. The purpose of this study was to examine the ways in which social aspects influenced a group of emerging adults' comics reading when they were children and/or teens. Data was collected by surveying and conducting semi-structured interviews with 34 emerging adults in the Southeast region of the United States about their comics reading histories. The research findings describe who the participants felt had the most impact on their comics reading, as well as the extent to which the participants felt that they belonged to a community of comics readers. Significantly, the participants' notion of comics readers as "nerds" emerged from the data, which the participants largely connected to gender, and which participant Lauren noted, "It's not something I've really thought about 'til now.'" The implications of these findings suggest that some of these participants felt that there was a social cost to comics reading. Suggestions for making comics reading more accessible for more readers are discussed.